Ricardo Palma, reader of Ventura Travada - Sánchez Martínez, César Félix (2020)
In the present article, Ricardo Palma’s condition as first literary reader of Suelo de Arequipa convertido en Cielo (ca.1750) by Ventura Travada (1695-1758) will be studied, as well as the form in which the two authors, from different hermeneutical horizons, interpret the discursive functionality of prodigiousness.